2020
DOI: 10.5902/1983465945216
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial skills and its relationship with MSMES performance

Abstract: Purpose – This research aimed to study the relationship between entrepreneurial skills and MSMEs (Micro Small and Medium Enterprises) performance.Design/methodology/approach – A quantitative and descriptive research was conducted, operationalized through a survey with 47 MSMEs entrepreneurs.Findings – (1) Most responding entrepreneurs seek opportunities, take calculated risks, and often demand quality and efficiency in their activities within the company. It can also be noted that they always pointed to being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several studies have shown that entrepreneurial orientation, which includes characteristics such as proactiveness, risk taking, and value creation, positively influences the performance of MSMEs (Sutono, 2023). Characteristics of MSME owners, such as seeking opportunities, being persistent, and maintaining contact with networks have been found to influence innovation and subsequently influence performance (Macedo et al, 2020). Marketing capabilities and entrepreneurial innovation have been identified as factors that can improve MSME performance, especially during difficult times such as the COVID-19 pandemic.…”
Section: ) Entrepreneurship and Sense Of Ownershipmentioning
confidence: 99%
“…Several studies have shown that entrepreneurial orientation, which includes characteristics such as proactiveness, risk taking, and value creation, positively influences the performance of MSMEs (Sutono, 2023). Characteristics of MSME owners, such as seeking opportunities, being persistent, and maintaining contact with networks have been found to influence innovation and subsequently influence performance (Macedo et al, 2020). Marketing capabilities and entrepreneurial innovation have been identified as factors that can improve MSME performance, especially during difficult times such as the COVID-19 pandemic.…”
Section: ) Entrepreneurship and Sense Of Ownershipmentioning
confidence: 99%